Golden bifid might improve diarrhea-predominant irritable bowel syndrome via microbiota modulation - Mei Luo; Qin Liu; Lin Xiao; Li-Shou Xiong (BMC, 2022)
Abstract Objective Gut microbiota might play a crucial role in the pathogenesis of irritable bowel syndrome (IBS), and probiotics supplement may be an effective treatment option. This study aims to explore the therapeutic effects of Golden bifid on the diarrhea-predominant IBS (IBS-D). Methods Twenty-one consecutive IBS-D patients were recruited based on Rome IV criteria. All patients took 2000 mg Golden bifid triple daily for 4 weeks. Gastrointestinal (GI) symptoms, psychological symptoms, small intestine bacterial overgrowth (SIBO) and fecal microbiota characteristics were evaluated in IBS-D patients before and after treatment. Results After 4-week treatment of Golden bifid, the GI symptoms such as abdominal pain (2.90 ± 1.04 vs. 1.90 ± 1.26, P = 0.002), abdominal distension (2.00 ± 1.34 vs. 1.29 ± 1.31, P = 0.007), diarrhea (3.24 ± 1.37 vs. 1.81 ± 1.21, P = 0.001), defecatory urgency (3.48 ± 1.03 vs. 2.33 ± 1.35, P = 0.000) and incomplete evacuation (2.71 ± 1.15 vs. 1.76 ± 1.26, P = 0.003) were significantly alleviated in IBS-D patients. The Self-Rating Depression Scale (SDS) decreased significantly (46.19 ± 11.36 vs. 43.33 ± 9.65, P = 0.041), and SIBO could be eradicated in 25% (4/16) of IBS-D patients with SIBO. Meanwhile, the abundance of Unclassified Lachnospiraceae and Dorea in genus level and Unclassified Lachnospiraceae, Bacterium Dorea, Bacterium Butyricicoccus and Dorea formicigenerans ATCC 27755 in species level were increased in fecal microbiota (P < 0.05). Conclusions Golden bifid could improve most of GI symptoms and depressive symptoms in IBS-D patients and eradicate a small proportion of SIBO in those IBS-D patients with SIBO. What's more, Golden bifid could also modulate the fecal microbiota in IBS-D patients, which implied that the Golden bifid might improve IBS-D via microbiota modulation.